A census and inventory of wild animals - Jerry Mauri (Global Journal of Ecology - Peertechz Publications, 2023)
The destruction of habitats in ecosystems, the rapid growth of the human population, and climate change have led to a decline in wildlife populations worldwide. It is therefore important to carry out a census and inventory of wild animal species, to determine their size, distribution, and status, especially in the context of accounting for forestry resources. Highlights are also given to the differences between a census and an inventory and how they are carried out. Such as censuses and inventories, how they help in monitoring and understanding animal populations, habitat changes, and developing conservation strategies, and how these approaches can be used to calculate the economic value of forests. This article concludes by discussing the impact of censuses and inventories on sustainable forest management and improving forest accounting by providing more accurate data. However, in carrying out the census and inventory of wild animals there are still obstacles such as limited funds, human resources, and adequate technology. So it is suggested that the need for support from the government, organizations and the community to increase the availability of resources needed to carry out censuses and inventories of wild animals.